Public Hearings in Environmental and Social Impact Assessment for Energy Sector Projects in Cameroon - Kengne, Cyrille Valence Ngouana; Menang Evouna, Serge Emeran; Bitondo, Dieudonné (Taylor and Francis, 2013)
In Cameroon, like in other countries, public hearings are the most common method of citizen involvement mentioned in Environmental and Social Impact Assessment (ESIA). To elicit various attributes of current practice and characteristics of these public hearings in Cameroon, with focus on access, process and outcomes, we used an interpretive approach. This research unveiled an array of problems, including shortcomings in public hearing practice, law and regulatory framework, limited access to information, and inconvenient location of reading rooms (depositories). Public hearings do take place in depositories but they do not provide participants with the opportunity for direct debate and consensus-building. This research demonstrated that, local economic stakes tend to take precedence over critical questioning during public hearing events. However, public hearings in Cameroon attest to the growing willingness to challenge ESIA reports that may be fully backed by the government. In order for public hearings to be worthwhile events in Cameroon, there is need to build credibility and mutual trust among stakeholders.